2020
DOI: 10.1101/2020.02.21.959692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medium spiny neurons activity reveals the discrete segregation of mouse dorsal striatum

Abstract: AbstractBehavioural studies differentiate the rodent dorsal striatum (DS) into lateral and medial regions based on their particular roles; however, anatomical evidence suggest that it is a unified structure. To understand striatal dynamics and basal ganglia functions, it is essential to clarify the circuitry that supports this behavioural-based segregation. Here, we show that the mouse DS is made of two non-overlapping functional circuits divided by a sharp boundary. Combining … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 112 publications
(175 reference statements)
1
7
0
Order By: Relevance
“…We show that both MSN types respond to bilateral whisker stimulation in awake mice. These results are in agreement with whole-cell recordings in anesthetized mice 16,21,23 . A previous study using whole-cell recordings in awake mice reported that sensory responses in dMSNs were markedly larger than in iMSNs 20 , which was not the case in our data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We show that both MSN types respond to bilateral whisker stimulation in awake mice. These results are in agreement with whole-cell recordings in anesthetized mice 16,21,23 . A previous study using whole-cell recordings in awake mice reported that sensory responses in dMSNs were markedly larger than in iMSNs 20 , which was not the case in our data.…”
Section: Discussionsupporting
confidence: 90%
“…Another mechanism could be an increase in MSN membrane conductance due to synaptic input during whisking, and lastly, a decreased synaptic driving force due to membrane depolarization in MSNs. For instance, during up-states in anesthetized mice, a brain state characterized by depolarization and elevated synaptic input, sensory stimulation generates smaller responses in the MSNs than those evoked in the down-state 16,21 . Our data show that during whisking, MSNs undergo depolarization and increase in membrane conductance (Figures 3 and S3), both supporting the attenuation of synaptic responses.…”
Section: Sensory Responses In Both Msn Types Were Attenuated By Whiskingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dStr is composed of molecularly, synaptically, and functionally distinct subdivisions (Flaherty and Graybiel, 1994;Smith et al, 2004;Palmiter, 2009, 2010;Pan et al, 2010;Nambu, 2011;Hintiryan et al, 2016;Hooks et al, 2018;Poulin et al, 2018;Martin et al, 2019;Alegre-Cortés et al, 2020;Ortiz et al, 2020). The dorsomedial striatum (DMS) and dorsolateral striatum (DLS) are thought to be involved in regulating goaldirected and habitual behavior, respectively (Yin and Knowlton, 2006;Balleine and O'Doherty, 2010;Redgrave et al, 2010;O'Hare et al, 2016;Malvaez and Wassum, 2018;Cox and Witten, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The dStr is composed of molecularly, synaptically, and functionally distinct subdivisions (Flaherty and Graybiel, 1994; Smith et al, 2004; Darvas and Palmiter, 2009, 2010; Pan et al, 2010; Nambu, 2011; Hintiryan et al, 2016; Hooks et al, 2018; Poulin et al, 2018; Martin et al, 2019; Alegre-Cortés et al, 2020; Ortiz et al, 2020). The dorsomedial striatum (DMS) and dorsolateral striatum (DLS) are thought to be involved in regulating goal-directed and habitual behavior, respectively (Yin and Knowlton, 2006; Balleine and O’Doherty, 2010; Redgrave et al, 2010; Cox and Witten, 2019).…”
Section: Introductionmentioning
confidence: 99%